The Relevance of Intellectual Capital Value in the Performance of Village-Owned Enterprises in the Tourism Sector - Yosi Mardoni; Noorina Hartati; Helmiatin Helmiatin; Ni Wayan Marsha Satyarini (AMAR (Andalas Management Review), 2021)
Village-owned enterprises (BUMDes) are village economic institutions with many obstacles in their journey, especially related to their performance. The primary purposes of this study are to analyze the performance of BUMDes from the perspective of intellectual capital and spiritual capital. A quantitative method with PLS-Structural Equation Modeling (SEM) was used to analyze this research. The research data was collected using purposive sampling, deliberately taking samples of several BUMDes to spread in Java island, Sulawesi island, Sumatra island, Maluku island, Kalimantan island, to Bangka Belitung island. The samples in this study were 129 respondents from several BUMDes that business unit in tourism village. The intellectual capital elements consist of human capital, spiritual capital, customer capital, and technology capital. This study indicates that human capital, spiritual capital, customer capital, and technology capital positively affect performance. Meanwhile, organizational capital does not influence performance